Narrativas sobre construcciones identitarias en una región norandina peruana* - Torres Villafane, Jessica Miriam (Pontificia Universidad Católica del Perú, 2023)
This paper aims to discuss the formation of identities in the Ancash region based on a Narrative Inquiry of two families living in the city of Huaraz, the parents are Hirka and Quyllur. Both have faced the same externalinfluences but have opted for different identity constructions. Narrative inquiry employs three dimensions: interaction, continuity, and situation. The data analysis was based on the composition of meanings and theinterpretative perspective of the experiences that consist of organizing meanings based on the data and a reflective process by the researcher, and the presentation of the advances to a support group to discuss, review and adjustment of the obtained data. From the analysis of the experiences, we can conclude that Hirka represents cultural resistance and Quyllur cultural assimilation. The first considers that their cultural practices have been inherited from their ancestors; on the other hand, Quyllur does not have this intergenerational awareness.

El presente trabajo pretende discutir la formación de identidades en el departamento de Áncash, basado en la investigación narrativa de dos familias que viven en la ciudad de Huaraz, los progenitores son Hirka y Quyllur. Ambos han enfrentado las mismas influencias externas pero han optado por construcciones identitarias diferentes. La investigación narrativa emplea tres dimensiones: interacción, continuidad y situación. El análisis de datos se basó en la composición de sentidos y la perspectiva interpretativa de las experiencias, que consta de organizar significados a partir de los datos y de un proceso reflexivo por parte del investigador, y la presentación de los avances del trabajo a un grupo de apoyo1 para la discusión, revisión y ajuste de la información obtenida. A partir del análisis de las experiencias, podemos concluir que Hirka representa la resistencia cultural y Quyllur la asimilación cultural. El primero considera que sus prácticas culturales han sido heredadas de sus ancestros; en cambio, Quyllur no tiene esta conciencia intergeneracional.
Narratives About Identity Constructions in a Peruvian Nor-Andean Region
Keywords: Identity; Quechua language; Symbolic representation; Andean religiosity; Narrative inquiry; Identidad; Lengua quechua; Representaciones simbólicas; Religiosidad andina; Investigación narrativa; https://purl.org/pe-repo/ocde/ford#5.04.03